ESTABLISHMENT OF EMPIRICAL FORMULAS FOR EVALUATING UNDERWATER SHOCK WAVES PARAMETERS IN SHALLOW SEA IN TRUONG SA ARCHIPELAGO - Loi, Vu Dinh; Tho, To Duc; Tuan, Le Anh; Nghi, Nguyen Cong (Vietnam Journal of Marine Science and Technology, 2015)
Surface pressure of shockwave and duration of compression phase are characteristic parameters for solving underwater explosion problems. According to reported researches, they are often calculated in a general water environment and rarely practiced in the seawater due to difficult conditions. This paper presents the experimental results of the underwater explosions in shallow sea in Truong Sa Archipelago and establishes empirical formulas for these parameters.